2012
DOI: 10.1029/2012sw000765
|View full text |Cite
|
Sign up to set email alerts
|

Reply to comment by Joseph E. Mazur and T. Paul O'Brien on “Analysis of GEO spacecraft anomalies: Space weather relationships”

Abstract: [1] The authors welcome the comment from J. E. Mazur and T. P. O'Brien [Mazur and O'Brien, 2012] on our recently published study [Choi et al., 2011]. In our paper, we investigated the geostationary Earth orbit (GEO) satellite anomalies archived by Satellite News Digest (SND) during 1997-2009 in order to search for possible influences of space weather on the anomaly occurrences. There were good relationships between geomagnetic activity (as measured by the Kp index) and anomaly occurrences of the GEO satellites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Even though modern satellites have benefited from the analysis of past flight anomalies and losses (Koons et al, ), surface charging remains a source of problems (Ferguson, ; Minow & Parker, ). A statistical analysis of the 95 commercial satellite anomalies provided by the Satellite News Digest (SND) website in the period of 1997–2009 showed the anomalies have a strong correlation with geomagnetic activity as monitored by the Kp index (Choi et al, ; Choi et al, ). Even though Mazur and O'Brien () indicated that a number of these anomalies were not related to the environment, the combined detailed analysis of Los Alamos National Laboratory (LANL) GEO spacecraft data made by Choi et al () and by Thomsen et al () indicated that anomalies are more likely to occur a) during higher values of Kp index, b) in the local time between premidnight through dawn; c) during the equinox seasons; d) during the declining phase of the solar cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Even though modern satellites have benefited from the analysis of past flight anomalies and losses (Koons et al, ), surface charging remains a source of problems (Ferguson, ; Minow & Parker, ). A statistical analysis of the 95 commercial satellite anomalies provided by the Satellite News Digest (SND) website in the period of 1997–2009 showed the anomalies have a strong correlation with geomagnetic activity as monitored by the Kp index (Choi et al, ; Choi et al, ). Even though Mazur and O'Brien () indicated that a number of these anomalies were not related to the environment, the combined detailed analysis of Los Alamos National Laboratory (LANL) GEO spacecraft data made by Choi et al () and by Thomsen et al () indicated that anomalies are more likely to occur a) during higher values of Kp index, b) in the local time between premidnight through dawn; c) during the equinox seasons; d) during the declining phase of the solar cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Choi et al . [, ] have identified a large set of spacecraft anomalies that occurred at geosynchronous orbit between 1997 and 2009, as reported in the Satellite News Digest. They presented a table of 95 anomalies of various types, including 32 for which event times (and therefore spacecraft locations) were known.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the Kp and seasonal dependence, and especially the local time dependence, Choi et al . [, ] concluded that the majority of satellite anomalies in their compilation were attributable to surface charging effects. For comparison with the statistical anomaly occurrence rates, they also analyzed Los Alamos energetic electron fluxes from geosynchronous orbit in the energy ranges of 50–75 keV, 225–315 keV, and 1.9–3.1 MeV.…”
Section: Introductionmentioning
confidence: 99%